UJI STABILITAS WARNA ANTOSIANIN EKSTRAK BUNGA TELANG PADA BERBAGAI PH DAN UJI POTENSI ANTIBAKTERI - Fitriani, Dewi; Novitasari, Aprilia Donna; Ariani, Lilies Wahyu (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Anthocyanins are flavonoid compounds that can be found in red, orange, purple, and blue coloured plants. The colour stability of these compounds is generally affected by temperature, pH and solvents. Anthocyanins tend to be stable at acidic pH and unstable at alkaline pH. Telang flower is a plant that has anthocyanin content. This anthocyanin content provides many benefits both in the health and food fields. The purpose of this study was to determine the effect of variations in solvent pH on the extraction of telang flowers on yield, extract pH, colour stability and to test antibacterial activity in extractions using alkaline solvents. This research method is to extract anthocyanins in telang flowers, using variations in solvent pH, then calculate the yield, pH of the extract, colour stability formed. This study also tested the potential antibacterial activity of extracts extracted using solvents in an alkaline atmosphere. The results showed that increasing the pH of the solvent increased the percent yield, the pH of the extract was obtained in the pH range of 4-8, with the anthocyanin content decreasing. The extract obtained has a different colour spectrum at each pH condition and the extract conditioned at alkaline pH has inhibitory activity against Staphylococcus aureus bacteria.